Diversification of the physical and sport education syllabi and its effects on the musculoskeletal system in young female students - Bendíková, Elena (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The prevalence of musculoskeletal disorders in the school-age population might lead to the occurrence of vertebrogenic diseases in adulthood, which stresses the importance of timely primary prevention in the form of health-oriented compensatory exercise programs. Aim of Study. This pilot study presents targeted diversification of physical and sport education syllabi focused on the improvement of the musculoskeletal system’s functions in young female students, including body posture, dynamic capacity of the spine, and the muscle system. Material and Methods. The study group comprised of 24 high school female students, divided into experimental (EG; 16.32 ± ± 0.32 years) and control (CG; 16.56 ± 0.56 years) groups. The data were acquired using standardized methods focused on the functional capacity of the musculoskeletal system. Results. In contrast to the control (V1-2) stage, the experimental (V3-4) stage involved diversification of physical and sport education syllabi for the EG subjects, which led to significant changes in their overall body posture (p < 0.01). The most significant changes occurred in the abdominal segment and pelvic inclination (p < 0.01). The dynamic capacity of the spine (p < 0.01), in all five tests, also changed in the EG participants. Bad movement habits affected the quality of the muscle system in the members of both groups. We noted the most significant changes (p < 0.01) in m. trapezius pars superior and m. levator scapulae, the muscles responsible for neck pain. The hip flexors contributed significantly (p < 0.05) to lower back pain. We found significant differences between the EG and the CG. The EG participants demonstrated improvements in all monitored segments. Conclusions. The results obtained by the EG significantly prove how important it is to diversify physical and sport education syllabi to improve health and the functional capacity of the musculoskeletal system in the school-aged population
Keywords: musculoskeletal system; physical and sports education; student